Relationship Between Physical Activity and Menopausal Symptoms Among Menopausal Women - Ahmed, Amany A.; Hafez, Samar K.; Gohar, Isis E. (International Journal For Research In Health Sciences And Nursing, 2019)
Background:The menopausal transition is known to play a major role in the etiology of various somatic, vasomotor, sexual and psychological symptoms. A large number of women are choosing not to take hormonal therapy, it is increasingly important to identify evidence-based lifestyle modifications. The aim was to assess the relation between the level of women activity and the severity of their menopausal symptoms. Methods:A descriptive correlational research design was utilized, conducted at four faculties selected randomly from all the theoretical faculties (namely art, commerce, law, tourism) affiliated to University. A convenience sample of (100) peri menopausal working women at the previously mentioned settings. Three tools were used to collect the necessary data. Tool (I): Socio - demographic and clinical data structured interview schedules, Tool (II): Menopause rating scale (MRS) was used to measure the severity of menopausal symptoms it compromises of 11 statements that are subdivided into three main groups; somatic, urogenital and psychological symptoms and Tool (III): International Physical Activity Questioner (IPAQ) short form, this tool was used to assess the physical activity of the women Results:more than two thirds (67%) of study participants aged between 51-55 years old. Also, itwas observed that level of activity of more than three fifths (65%) of the women in this study was low compared to 35% of them their level of activity was moderate.Moreover. A non-significant negative correlation was found between participants’ level of activity and their somatic, psychological as well as total score of menopausal symptoms {-.065 (.521), -.172(.088) &-.108 (.284)} respectively. Conclusion:the results of the present study supported the research hypothesis as moderate level of activity was associated with decreased severity of menopausal symptoms in general and severity of somatic and psychological symptoms in particular.